Between the caves and the sea: the Late Glacial occupation of the English East Midlands - Kotthaus, JK (2022)
This thesis investigates the degree of intensity of Late Glacial human occupation of open landscapes in the English East Midlands, including evidence for chronological and regional patterns in the timing of human re-occupation and presence during the Late Glacial Interstadial (GI-1e-a; c. 14,700 to 12,900 BP; Rasmussen et al. 2014:Table 1). The regional focus is on the open, low-lying landscapes situated between known Late Upper Palaeolithic cave sites in central England and the present-day North Sea coast. Emphasis is placed on the identification of preferential site location patterns in riverine and lacustrine environments, as investigated through two site datasets comprising data from legacy site archives, Historic Environment Records, and the Portable Antiquities Scheme. Further attention has been directed towards lithic typological and technological attribute analyses of three open-air site assemblages (Farndon Fields, Nottinghamshire, Seamer Carr K, North Yorkshire, and Risby Warren, North Lincolnshire).